A Comparison of the Braking and Propulsion Phase Characteristics of Traditional and Accentuated Eccentric Loaded Back Squats in Resistance-Trained Women - Brookelyn A. Campbell; Conor J. Cantwell; Lauren K. Marshall-Ciochon; Zachary S. Schroeder; Adam E. Sundh; Jack B. Chard; Christopher B. Taber; Timothy J. Suchomel (Applied Sciences)
The aim of this study was to compare the braking and propulsion force–time and barbell velocity characteristics between back squat sets performed using traditional (TRAD) or accentuated eccentric loading (AEL) in resistance-trained women. In total, 14 participants completed four separate testing sessions that included a one repetition maximum (1RM) back squat and three squat testing sessions that used either TRAD or AEL. During the squat testing sessions, participants performed sets of three back squat repetitions using TRAD loads with 50, 60, 70, and 80% 1RM or performed the same loads with the addition of weight releasers that equated the total load to 100% (AEL-MAX) or 110% (AEL-SUPRA) 1RM during the eccentric phase of the first repetition of each set. Braking and propulsion mean force, duration, and impulse as well as mean and peak barbell velocity were examined across each back squat set. Significantly greater braking impulses were produced during the AEL conditions across all loads (p < 0.02), while greater braking mean force during AEL-SUPRA was produced compared to TRAD during with 50 and 60% 1RM (p < 0.02). There were no other significant differences in braking, propulsion, or barbell velocity that existed between different conditions (p > 0.05). AEL-MAX and AEL-SUPRA provide a greater braking stimulus compared to TRAD squats, while the propulsion phase may not be significantly impacted. Rapid and maximal force production may be favored by larger and smaller load spreads, respectively.